2023
DOI: 10.3390/life13010153
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, Potassium, Sodium, and Magnesium Concentrations in the Placenta, Umbilical Cord, and Fetal Membrane from Women with Multiple Pregnancies

Abstract: Calcium (Ca), potassium (K), sodium (Na), and magnesium (Mg) are the elements responsible for the fundamental metabolic and biochemical processes in the cells of the body. The demand for these elements increases significantly during pregnancy, where an adequate supply protects women from the hypertension common in pre-eclampsia and preterm labor. This study aimed to evaluate the association between macro-elements (Ca, Mg, Na, and K) in the placenta, fetal membrane, and umbilical cord and the morphometric param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 79 publications
0
7
0
2
Order By: Relevance
“…When compared to the reported case of species of capsicum as reported by Ogunlade et al 16 , Capsicum frutescens (1.21%), Capsicum annum (3.03%), Capsicum annum (1.62%) and Capsicum frutescens (2.12%), the ash contents were higher than these reported case. The proximate contents of Capsicum chinense as reported by Sharma et al 18 showed moisture (8.43±0.20%), protein (8.2±0.15* %) and crude fiber (29.26±0.03%) were higher than the results of the study by Grzeszczak et al 19 , had reported the protein, crude fiber and ash contents of Capsicum chenense foliage to be 1.20±0.00 e %, 2.90±0.14 a % and 2.00±0.00 d %. The observable differences in the results could be linked to some factors such as climatic conditions, soil conditions and the age of the land used for farming.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…When compared to the reported case of species of capsicum as reported by Ogunlade et al 16 , Capsicum frutescens (1.21%), Capsicum annum (3.03%), Capsicum annum (1.62%) and Capsicum frutescens (2.12%), the ash contents were higher than these reported case. The proximate contents of Capsicum chinense as reported by Sharma et al 18 showed moisture (8.43±0.20%), protein (8.2±0.15* %) and crude fiber (29.26±0.03%) were higher than the results of the study by Grzeszczak et al 19 , had reported the protein, crude fiber and ash contents of Capsicum chenense foliage to be 1.20±0.00 e %, 2.90±0.14 a % and 2.00±0.00 d %. The observable differences in the results could be linked to some factors such as climatic conditions, soil conditions and the age of the land used for farming.…”
Section: Resultsmentioning
confidence: 52%
“…The zinc content of flesh was the highest (9.32±0.01** mg kgG 1 ). The significance of sodium, calcium, potassium, magnesium and iron has been reported by scholars such as 12,19,20 . The K is essential in the regulation of acid-base and water balance of the cells 20 .…”
Section: Mineral and Electrolyte Discussionmentioning
confidence: 90%
“…Our findings showed a U-shaped relationship between maternal serum Na levels and the risk of preterm birth. As the most important electrolyte in extracellular fluid, Na regulates the osmolality in the extracellular space and plays a crucial role during pregnancy (39). Decreased maternal Na levels during pregnancy may lead to an enhancement of the renin angiotensin system, which promotes cardiovascular and renal injury mechanisms (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been observed that the serum calcium concentration may be useful in the prediction of preterm delivery, but it should be emphasized that this relationship was considered independent of the magnesium status. Grzeszczak et al studied multiple pregnancies and observed a strong significant positive correlation between calcium and magnesium concentrations in the umbilical and the fetal membrane as well as between umbilical cord magnesium concentrations and the length of the pregnancy [ 47 ].…”
Section: Discussionmentioning
confidence: 99%